2016
DOI: 10.2340/00015555-2185
|View full text |Cite
|
Sign up to set email alerts
|

Kaposiform Haemangioendothelioma-spectrum Lesions with Kasabach-Merritt Phenomenon: Retrospective Analysis and Long-term Outcome

Abstract: Kasabach-Merritt phenomenon (KMP) is a rare life-threatening vascular condition of infancy. Prognosis factors and long-term follow-up data are lacking. We retrospectively analysed the records of 24 infants (10 females, 14 males) treated for KMP in the Department of Dermatology of Necker-Enfants Malades Hospital, Paris, France, from 1984 to 2012. Mean duration of thrombocytopaenia (2,000-38,000 platelets/mm3, mean 10,500/µl) was 8.8 months (range 3 days-84 months), which correlated with tumour infiltration dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 19 publications
1
42
0
2
Order By: Relevance
“…Dear Editor , Kasabach–Merritt phenomenon (KMP) is a very rare life‐threatening condition that combines a vascular tumour belonging to the kaposiform haemangioendothelioma (KHE) spectrum, lesions and thrombocytopenia . Thrombocytopenia results from platelet trapping within the tumour.…”
Section: Clinical and Biological Features Of Patients Treated With Simentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Editor , Kasabach–Merritt phenomenon (KMP) is a very rare life‐threatening condition that combines a vascular tumour belonging to the kaposiform haemangioendothelioma (KHE) spectrum, lesions and thrombocytopenia . Thrombocytopenia results from platelet trapping within the tumour.…”
Section: Clinical and Biological Features Of Patients Treated With Simentioning
confidence: 99%
“…This coagulopathy is frequently protracted after thrombocytopenia resolution. Several treatments have been proposed with variable efficiency . Sirolimus is a mammalian target of rapamycin inhibitor.…”
Section: Clinical and Biological Features Of Patients Treated With Simentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor , Kaposiform haemangioendothelioma (KHE) is a locally aggressive vascular tumour that occurs mainly during childhood and invades adjacent tissue and organs . It is commonly complicated by Kasabach–Merritt phenomenon (KMP), in about 50–70% of cases .…”
mentioning
confidence: 99%
“…Sirolimus is an inhibitor of mammalian target of rapamycin that has recently been prescribed off‐label for KHE. Several studies have demonstrated a beneficial effect of sirolimus for KHE, but the numbers of patients were small and the treatment and follow‐up periods were short. Here we retrospectively analysed a cohort of 22 patients with KHE with KMP who were treated with sirolimus for compassionate use.…”
mentioning
confidence: 99%